A study on overturning failure of horizontally curved single steel box girders. (March 2019) - Lee, Keesei; Andrawes, Bassem; Lim, Jeonghyeon; Kim, Heesoo; Kang, Youngjong
Abstract: A horizontally curved girder is subjected to bending and torsional moments simultaneously because of its initial curvature (even under gravitational load only). A negative reaction force can be introduced in some cases because of the torsional moment. Since the reaction force at each support is strongly related to stability problem of the whole structure, it has been checked for individual construction stage at the design time. The superstructure of a simply supported curved bridge in South Korea was overturned during the casting of a concrete barrier (placed on the convex side of the concrete slab). After the failure, it was reported that reaction forces were checked at the design stage and an overturning stability warning was not issued as there was no negative reaction force at any of the bearings during the construction stages. This study investigates the cause of the overturning failure. Possible failure scenarios were assumed and each was analyzed. In this research, the construction process was departmentalized into seven steps (only three steps were considered at the design stage). Finally, behavior characteristics due to the construction progress were discussed based on analysis of the results. Highlights: This paper reviewed an overturning failure accident in Korea. Possible failure scenarios were discussed through numerical analyses. The real bridge model was analyzed based on field survey data after failure. In order to investigate the dominant reason of failure, detailed construction process was considered.